Perlindungan Hukum Korban Kekerasan Dalam Rumah Tangga (KDRT) - Bima Guntara; Ayni Suwarni Herry; Ari Widiarti (CV. Multi Kreasi Media, 2023)
Domestic violence is an act of violence against women that is often invisible. Along with the increasing cases of domestic violence, the government issued a law on the Elimination of Domestic Violence, with the aim that victims of domestic violence, especially women, are expected to obtain legal protection. The problem that arises then is how to legally protect victims of Domestic Violence (KDRT) to prevent domestic violence crimes. The existence of Law Number 23 of 2004 concerning the Elimination of Domestic Violence is expected to be able to provide legal protection for victims of Domestic Violence (KDRT) significantly. The forms of protection provided for in this Law are temporary protection from the police, court protection and placement of victims in